Scene perception in posterior cortical atrophy: categorization, description and fixation patterns - Shakespeare, Timothy J.; Yong, Keir X.; Frost, Chris; Kim, Lois G.; Warrington, Elizabeth K.; Crutch, Sebastian J. (Frontiers in Human Neuroscience, 2013)
Partial or complete Balint’s syndrome is a core feature of the clinico-radiological syndrome of posterior cortical atrophy (PCA), in which individuals experience a progressive deterioration of cortical vision. Although multi-object arrays are frequently used to detect simultanagnosia in the clinical assessment and diagnosis of PCA, to date there have been no group studies of scene perception in patients with the syndrome. The current study involved three linked experiments conducted in PCA patients and healthy controls. Experiment 1 evaluated the accuracy and latency of complex scene perception relative to individual faces and objects (colour and greyscale) using a categorisation paradigm. PCA patients were both less accurate (faces<scenes<objects) and slower (scenes<objects<faces) than controls on all categories, with performance strongly associated with their level of basic visual processing impairment; patients also showed a small advantage for colour over greyscale stimuli. Experiment 2 involved free description of real world scenes. PCA patients generated fewer features and more misperceptions than controls, though perceptual errors were always consistent with the patient’s global understanding of the scene (whether correct or not). Experiment 3 used eye tracking measures to compare patient and control eye movements over initial and subsequent fixations of scenes. Patients’ fixation patterns were significantly different to those of young and age-matched controls, with comparable group differences for both initial and subsequent fixations. Overall, these findings describe the variability in everyday scene perception exhibited by individuals with PCA, and indicate the importance of exposure duration in the perception of complex scenes.